Production and Extraction of Siderophores-Catecholate- from -MDR-Acinetobacter baumannii - Baghdad Science Journal (مجلة بغداد للعلوم)
Siderophores are low molecular weight organic compounds produced by microorganisms growing under low iron concentration.In this study we describe the detection, production and extraction of siderophores secreted by Acinetobacter baumannii (Multiple-drug resistant ) pathogens. One hundered twenty Gram –negative non lactose fermenter bacilli isolates have been collected from three hospitals at Baghdad city over three months. Primary identification of these isolates is performed by standard diagnostic methods (biochemical tests and API 20 NE); 19 clinical isolates of A. baumannii are cultured on CHROMagar (highly selective medium for detection of MDR Acinetobacter) as well as diagnoses is documented by using Vitek 2 system. Isolates are examined towards 11 different antibiotics. High resistance is recognized for most isolates. Detection of siderophore has been done by examining the isolates on M9 minimum medium; 5 isolates (26%) are producers for siderophore, the highest producing one is isolated from sputum and chosen to extract siderophore catecholate . (Ab5S) isolate is examined on specific synthetic medium for production then siderophore molecules are extracted by ethyl acetate .Weight of dried extract is determined (115 mg/ml) and siderophore chemical nature has been assessed which appeared as catecholate.